Fecal Microbiota Transplantation Reshapes the Physiological Function of the Intestine in Antibiotic-Treated Specific Pathogen-Free Birds - Li, Peng; Gao, Mingkun; Song, Bochen; Liu, Yan; Yan, Shaojia; Lei, Jiaqi; Zhao, Yizhu; Li, Guang; Mahmood, Tahir; Lv, Zengpeng; Hu, Yongfei; Guo, Yuming (Frontiers in Immunology, 2022)
The topic about the interactions between host and intestinal microbiota has already caught the attention of many scholars. However, there is still a lack of systematic reports on the relationship between the intestinal flora and intestinal physiology of birds. Thus, this study was designed to investigate it. Antibiotic-treated specific pathogen-free (SPF) bird were used to construct an intestinal bacteria-free bird (IBF) model, and then, the differences in intestinal absorption, barrier, immune, antioxidant and metabolic functions between IBF and bacteria-bearing birds were studied. To gain further insight, the whole intestinal flora of bacteria-bearing birds was transplanted into the intestines of IBF birds to study the remodeling effect of fecal microbiota transplantation (FMT) on the intestinal physiology of IBF birds. The results showed that compared with bacteria-bearing birds, IBF birds had a lighter body weight and weaker intestinal absorption, antioxidant, barrier, immune and metabolic functions. Interestingly, FMT contributed to reshaping the abovementioned physiological functions of the intestines of IBF birds. In conclusion, the intestinal flora plays an important role in regulating the physiological functions of the intestine.